2020
DOI: 10.1002/jcp.29630
|View full text |Cite
|
Sign up to set email alerts
|

CCAT2 contributes to hepatocellular carcinoma progression via inhibiting miR‐145 maturation to induce MDM2 expression

Abstract: Long noncoding RNA colon cancer-associated transcript 2 (CCAT2) has been recently found to function as an oncogene in hepatocellular carcinoma (HCC).However, the mechanisms of CCAT2 in HCC development remain to be further explored. In the present study, we found that CCAT2 was abnormally upregulated in HCC cells and tissue specimens, exhibiting an inverse correlation with microRNA (miR)-145 expression. Mechanistic investigation showed that CCAT2 selectively blocked miR-145 processing, leading to decreased matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In line with our findings, a recent study on hepatocellular carcinoma (HCC) showed that in HCC cells with miR-145 overexpression, the expression level of p53 and p21 will enhance in comparison with control cells. p53 and p21 are considered the most critical checkpoints of the Gap1/Synthesis (G1/S) phase, which link with the complex of Cyclin-Dependent Kinase 6 (CDK6)/CyclinD1, interrupt with Cyclin-Dependent Kinases (CDKs), and consequently lead to cell cycle arrest [ 65 ]. Also, since the miR-145 binding sites are fit for the 3′-untranslated region (UTR) of the oncogene mouse double minute 2 (MDM2), it is regarded as a possible miR-145 target.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with our findings, a recent study on hepatocellular carcinoma (HCC) showed that in HCC cells with miR-145 overexpression, the expression level of p53 and p21 will enhance in comparison with control cells. p53 and p21 are considered the most critical checkpoints of the Gap1/Synthesis (G1/S) phase, which link with the complex of Cyclin-Dependent Kinase 6 (CDK6)/CyclinD1, interrupt with Cyclin-Dependent Kinases (CDKs), and consequently lead to cell cycle arrest [ 65 ]. Also, since the miR-145 binding sites are fit for the 3′-untranslated region (UTR) of the oncogene mouse double minute 2 (MDM2), it is regarded as a possible miR-145 target.…”
Section: Discussionmentioning
confidence: 99%
“…Also, since the miR-145 binding sites are fit for the 3′-untranslated region (UTR) of the oncogene mouse double minute 2 (MDM2), it is regarded as a possible miR-145 target. In both HCC cells and tumor tissues, the mRNA level of MDM2 is significantly increased which is inversely associated with miR-145 expression [ 65 ]. Also, it is reported that miR-145 overexpression would decrease the expression level of MDM2 mRNA and protein.…”
Section: Discussionmentioning
confidence: 99%
“…The CCAT2/miR-145 regulation axis was also described in HCC progression via modulation of the MDM2 gene [45]. MDM2 is an oncogene previously reported in epithelial cancers, high-grade tumors, being a signature biomarker in multiple soft tissues [114].…”
Section: Cerna Activity Of Ccat2 and Mirna Spongingmentioning
confidence: 91%
“…Recent studies have also highlighted CCAT2 as having multiple miRNA regulatory targets (Figure 2, Table 1), acting as one of the main pro-neoplastic drivers in various human cancers [39,[41][42][43]. For example, CCAT2 promotes its neoplastic regulatory functions through extensive ceRNA networks involving multiple tumor suppressor miRNAs, including miR-424, miR-145, miR-23b-5p, and miR-143 [39,42,[44][45][46].…”
Section: Cerna Activity Of Ccat2 and Mirna Spongingmentioning
confidence: 99%
“…Exosomes play an important role in the tumor microenvironment and mediate the interaction between pancreatic cancer cells (PC) and matrix components, including pancreatic stellate cells (PSC), to regulate the progression of pancreatic cancer [56]. Primary PSC was isolated from PC patients and demonstrated that exosomes derived from PSC can be internalized by PC cells to promote cell proliferation.…”
Section: Circulating Mirnasmentioning
confidence: 99%